OP0244 Sustained Suppression of Rheumatoid Arthritis Disease Markers by Mavrilimumab but Not Golimumab in Anti-Tumor Necrosis Factor-Inadequate Responders: An Exploratory Analysis in The Phase IIB Earth Explorer 2 Clinical Trial. (15th July 2016) - Guo, X.; Wang, S.; Bay-Jensen, A.C.; Karsdal, M.A.; Godwood, A.; Close, D.; Ryan, P.C.; Roskos, L.K.; White, W.I.
Abstract : Background: Treatment of rheumatoid arthritis (RA) patients by anti-tumour necrosis factors (anti-TNFs), such as golimumab, has substantially improved patient outcomes. However, unmet therapeutic needs exist for the significant proportion of patients who do not respond to current biologics treatment. Mavrilimumab is a fully human monoclonal antibody which inhibits the granulocyte-macrophage colony-stimulating factor receptor α (GM–CSFR-α). Recently, a Phase IIb study has been completed to evaluate the efficacy and safety of mavrilimumab and golimumab in both disease-modifying antirheumatic drug (DMARD)-inadequate responder (IR) and anti-tumor necrosis factor-inadequate responders (anti-TNF-IR) patients (EARTH EXPLORER 2, NCT01715896 ). Objectives: To assess peripheral biomarkers and pathophysiological pathways modulated by mavrilimumab in comparison with golimumab in both DMARD-IR and anti-TNF-IR RA patients. Methods: In total, 75 DMARD-IR and 63 anti-TNF-IR patients were randomized in a 1:1 ratio to receive subcutaneous 100 mg mavrilimumab (n=70) every other week (Q2W) or 50 mg golimumab (n=68) Q2W alternating with placebo, in combination with methotrexate (7.5–25.0 mg/week) for 24 weeks. Serum levels of 18 RA-associated proteins as well as 3 protease-derived protein fragments were measured in 71 DMARD-IR and 61 anti-TNF-IR RA patients at baseline and 4 time points post-administration. Transcriptome sequencing was used to measure gene expression changes in whole blood of RA patients at baseline and day 169 post-administration. Results: Serum levels of CCL22 and CCL17 were suppressed by mavrilimumab but not golimumab, while CXCL13 and ICAM1 levels were suppressed by golimumab but not mavrilimumab. Those four proteins may be specific pharmacodynamic markers for the two biologics respectively. More interestingly, both mavrilimumab and golimumab demonstrated early and sustained suppression of multiple inflammatory markers in DMARD-IR patients, including CRP, SAA, MMP1, MMP3, IL6, VEGF, IL2R, and CD163. However, golimumab-induced early changes rapidly returned towards baseline levels in anti-TNF-IR patients, while serum protein suppression by mavrilimumab was maintained through day 169 in anti-TNF-IR patients. Similarly, mavrilimumab administration was associated with durable suppression of extracellular matrix markers, C1M, C3M, and P4NP7S, while golimumab only induced a transient change of the three markers in anti-TNF-IR patients. Furthermore, RNA sequencing results demonstrated significant regulation of 1547 transcripts at day 169 after mavrilimumab administration while golimumab had no impact on whole blood gene expression in anti-TNF-IR patients. In contrast, significant changes of 1042 and 2058 transcripts were observed in DMARD-IR patients at day 169 after mavrilimumab and golimumab administration respectively. Conclusions: Our study demonstrated sustained suppression of RA disease markers by mavrilimumab but not golimumab in anti-TNF-IR patients, suggesting the potential of greater long-term disease control by mavrilimumab than golimumab in this population of RA patients. Disclosure of Interest: X. Guo Shareholder of: MedImmune/AstraZeneca, Employee of: MedImmune/AstraZeneca, S. Wang Shareholder of: MedImmune/AstraZeneca, Employee of: MedImmune/AstraZeneca, A. Bay-Jensen Employee of: Nordic Bioscience, M. Karsdal Employee of: Nordic Bioscience, A. Godwood Shareholder of: MedImmune/AstraZeneca, Employee of: MedImmune/AstraZeneca, D. Close Shareholder of: MedImmune/AstraZeneca, Employee of: MedImmune/AstraZeneca, P. Ryan Shareholder of: MedImmune/AstraZeneca, Employee of: MedImmune/AstraZeneca, L. Roskos Shareholder of: MedImmune/AstraZeneca, Employee of: MedImmune/AstraZeneca, W. White Shareholder of: MedImmune/AstraZeneca, Employee of: MedImmune/AstraZeneca